2018
DOI: 10.1073/pnas.1705927115
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of a rice TPR-domain RNA-binding protein confers broad-spectrum disease resistance

Abstract: SignificanceCrops carrying broad-spectrum resistance loci provide an effective strategy for controlling infectious disease. Despite their importance, few broad-spectrum resistance loci have been reported, and the underlying mechanisms controlling the trait remain largely unknown. This report describes the identification of a gene, called “bsr-k1,” conferring broad-spectrum resistance and demonstrates that the encoded protein regulates immunity-related genes. Loss of function of BSR-K1 in rice leads to enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
127
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 37 publications
0
127
0
3
Order By: Relevance
“…Interestingly, various genes involved in BSR have been discovered in crops [197], only a few have been utilized due to consequent yield penalty [35,198] and none of the BSR genes formerly identified, coding for proteins possessing RNA-binding activity by [108,[199][200][201]. However, Zhou X. et al [202] identified broad spectrum resistance Kitaake-1 (bsr-k1) mutant conferring BSR against X. oryzae pvoryzae and Magnaporthe oryzae with no consequent effect on yield in rice. It was revealed that the mRNAs of OsPAL genes which are associated with defense in plants was bounded by bsr-k1 protein, thus, promoting their turnover.…”
Section: Pals: Emerging Key Players In Broad Spectrum Disease Resistancementioning
confidence: 99%
“…Interestingly, various genes involved in BSR have been discovered in crops [197], only a few have been utilized due to consequent yield penalty [35,198] and none of the BSR genes formerly identified, coding for proteins possessing RNA-binding activity by [108,[199][200][201]. However, Zhou X. et al [202] identified broad spectrum resistance Kitaake-1 (bsr-k1) mutant conferring BSR against X. oryzae pvoryzae and Magnaporthe oryzae with no consequent effect on yield in rice. It was revealed that the mRNAs of OsPAL genes which are associated with defense in plants was bounded by bsr-k1 protein, thus, promoting their turnover.…”
Section: Pals: Emerging Key Players In Broad Spectrum Disease Resistancementioning
confidence: 99%
“…Kitaake has been used to establish multiple mutant populations, including an RNAi mutant collection [6], T-DNA insertion collections [4], [7], and a whole-genome sequenced mutant population of KitaakeX, a Kitaake variety carrying the Xa21 immune receptor gene (formerly called X.Kitaake) [8, 9]. Kitaake has been used to explore diverse aspects of rice biology, including flowering time [10], disease resistance [11], [12], [13], small RNA biology [14], and the CRISPR-Cas9 and TALEN technologies [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…We also show here that the G5-TPR alone does not interact with RNA, irrespectively of whether it consisted of single or double stranded molecules, short hairpins, long stem-loops, or DNA ( Figure 3). This result establishes a main difference with proteins carrying TPR domains involved in RNA-dependent pathways or in direct RNA-binding (Abbas et al, 2013;Grotwinkel et al, 2014;Johnson et al, 2018;Katibah et al, 2013;Yang et al, 2012;Zhou et al, 2018). The high sequence conservation of the TPR-like domain strongly suggests that the dimerization module of Gemin5 plays a fundamental role for the architecture and activity of the protein.…”
Section: Discussionmentioning
confidence: 82%